Pendidikan Karakter Berbasis Pesantren di SD Al Mujtamak Pamekasan - - Mujtahidin; Badrud Tamam (Widyagogik)
The study with title of “Character Based Education Islamic Elementary School in Al Mujtamak of Pamekasan” have to explore the character based education model in Islamic Elementary School Al Mujtamak of Pamekasan. This study is qualitative with the aim of exploratory research which is the main instrument to acquire and explore the breadth and depth of data. The result of this study showed that the character based education model in elementary school Al Mujtamak of Pamekasan using character based education culture design and is supported by character based education community design, through moral values and religious that are implicitly to all eyes lessons. In practice, the teacher plays a very important because teachers must be able to create a conducive atmosphere for learning and be able to set an example in the formation of student character.